The interplay between cognitive load and self-efficacy in English-Medium Instruction (EMI) higher education - Emre Koca (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
English-Medium Instruction (EMI) has expanded rapidly across global higher education, yet the cognitive and psychological pressure that it places on non-native speakers remains a major concern. This study investigates the relationship between cognitive load—specifically its intrinsic and extraneous dimensions—and academic self-efficacy. Data were gathered from sixty university students using a thirty-item questionnaire. The analysis employed descriptive statistics, one-sample t-tests, and Pearson correlation to measure how instructional demands influence student confidence. The findings indicate that students experience high levels of cognitive load, which appear to place additional demands on their mental resources. Statistical tests confirmed these scores were significantly different from a neutral value, indicating a consistent pattern of mental strain. Most importantly, a negative correlation was identified, suggesting that as the instructional and mental burden increases, student belief in their own academic capability declines. These results suggest that language barriers and disorganized teaching materials may further contribute to learning difficulties and make learning more challenging for students. In order to enhance the effectiveness of EMI, institutions need to adopt a more language-sensitive pedagogy that reduces students' cognitive load and provides them with stronger psychological support.